Liquid chromatography-tandem mass spectrometry for monitoring vitamin D hydroxymetabolites in human aqueous humor. Issue 41 (8th October 2019) - Fabregat-Cabello, Neus; Darimont, Pierre; Huyghebaert, Loreen; Reynier, Pascal; Annweiler, Cédric; Milea, Dan; Le Goff, Caroline; Cavalier, Étienne
Abstract : A stable isotope dilution liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed for the determination of 24, 25-dihydroxyvitamin D3 (24, 25(OH)2 D3 ) and 25-hydroxyvitamin D3 /D2 (25(OH)D3 /D2 ) in human aqueous humor samples. Abstract : A stable isotope dilution liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed and validated for the determination of 24, 25-dihydroxyvitamin D3 (24, 25(OH)2 D3 ) and 25-hydroxyvitamin D3 /D2 (25(OH)D3 /D2 ) in human aqueous humor samples from the Eye-D study. Optimum sample preparation is based on simple liquid–liquid extraction (LLE) followed by derivatization with an Amplifex reagent prior to LC-MS/MS in order to enhance analyte sensitivity. The average recoveries for 24, 25(OH)2 D3 (0.02, 0.05, 0.4 μg L −1 ), 25(OH)D3 (0.2, 0.5, 3.75 μg L −1 ) and 25(OH)D2 (0.15, 0.4, 3 μg L −1 ) ranged from 92 to 112 with a coefficient of variance (CV) lower than 15%. The limits of quantitation (LOQs) were from 0.02 μg L −1 (24, 25(OH)2 D3 ) to 0.2 μg L −1 (25(OH)D3 ) using a sample volume of 50 μL. We demonstrated that the present method provides adequate sensitivity, selectivity, accuracy, and robustness to screen for vitamin D metabolites in aqueous humor samples by analyzing five samples which were withdrawn during cataract operation.